Exosomes Secreted by Nucleus Pulposus Stem Cells Derived From Degenerative Intervertebral Disc Exacerbate Annulus Fibrosus Cell Degradation via Let-7b-5p - Zhuang, Yin; Song, Sheng; Xiao, Dan; Liu, Xueguang; Han, Xiaofei; Du, Shihao; Li, Yuan; He, Yanming; Zhang, Shujun (Frontiers in Molecular Biosciences, 2022)
The pathogenesis of intervertebral disc degeneration (IDD) is complex and remains unclear. Nucleus pulposus stem cells (NPSCs) and annulus fibrosus cells (AFCs) play a critical role in the maintenance of intervertebral disc structure and function. Exosome-mediated miRNAs regulate cell proliferation, differentiation, apoptosis, and degradation. However, it is not clear whether the degenerative intervertebral disc-derived nucleus pulposus stem cells (D-NPSCs) can regulate the function of AFCs by delivering exosomes. Here we show that exosomes secreted by nucleus pulposus stem cells derived from degenerative intervertebral disc (D-DPSC-exo) can exacerbate AFC degeneration via inhibiting cell proliferation, migration, matrix synthesis, and promoting apoptosis. Specifically, let-7b-5p was highly expressed in D-DPSC-exo. Transfection of let-7b-5p mimic was found to promote apoptosis and inhibit proliferation migration and matrix synthesis of AFCs. In addition, transfection with let-7b-5p inhibitor caused the effect of D-DPSC-exo on AFCs to be reversed. Furthermore, we found that D-DPSC-exo and let-7b-5p inhibited IGF1R expression and blocked the activation of PI3K-Akt pathway. Results suggested that NPSC-exo exacerbated cell degeneration of AFCs via let-7b-5p, accompanied by inhibition of IGF1R expression and PI3K-Akt pathway activation. Therefore, insights from this work may provide a clue for targeted molecular therapy of intervertebral disc degeneration.